Project based learning to enhance speaking skills of seventh graders. - Muñoz Ponce, Carlos Andrés (2025)
This study investigates the effectiveness of Project-Based Learning (PBL) in enhancing the English language speaking skills among seventh graders in the school Veinticuatro de Julio located in Santa Elena. The research involved implementing a series of PBL activities designed to promote active learning and language practice. The mixed-method approach was applied to evaluate the students’ progress in the speaking skill. The phenomenon was observed systematically through a questionnaire that served to measure the preference of students on their experiences with PBL and conventional activities. Data was collected in teaching practice through multiple methods: pre- and post-speaking assessments, which measured fluency, accuracy, and vocabulary usage. The 41 participating students demonstrated improvements in their oral skills and exhibited greater confidence in front of an audience. The results highlight the effectiveness of PBL as a teaching strategy for developing English language-speaking skills and underscore that implementing PBL can positively impact students’ English-speaking skills offering valuable implications for language instruction practices.